PENERAPAN MODEL PEMBELAJARAN COOPERATIF INTEGRATED READING AND COMPOSITION (CIRC) DENGAN MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI IPA SMAN 1 BOJONGSOANG PADA MATERI SISTEM EKSKRESI - meti maspupah; Ara Hidayat; Rosiana Latifah (Jurnal BIOEDUIN, 2018)
The low ability of students to ask questions, express idea and record well and quickly make the students less focus on the material presented by the teacher. This situation lead the researchers to apply Cooperative Integrated learning model Reading and Composition (CIRC) with Mind Mapping. The objectives of this study is to describe the learning process of teachers and students as well as to analyze students' critical thinking skills by using Cooperative Integrated Reading And Composition (CIRC) model with Mind Mapping on grade XI IPA SMAN 1 Bojongsoang. This research used Pre-Experiment method with One Group Pretest-Posttest design. Analysis of research data include normality test, t-test or wilcoxon test. The results showed that RPP validation is very feasible to be used in learning with percentage of 91.3%, and the implementation of teacher and student learning is very good. Wilcoxon test showed that Cooperative Integrated Reading And Composition (CIRC) learning model with Mind Mapping can give positive contribution to students' critical thinking ability on excretory system material.